دور الإعلام الإسلامي في مكافحة الإرهاب: The Role of Islamic Media in Combating Terrorism - Abdul Malik, Ahmed (‘Abqari Journal, 2020)
يتعرض العالم اليوم لويلات الإرهاب لم يسبق لها مثيل في تاريخ البشرية، وكانت تلك الويلات تنبت وتنمو للأسف الشديد من أوكار المنظمات والتنظيمات والتيارات والجماعات الإرهابية التي تنتسب الى الإسلام بغير حق، إنّ تكثيف حضورها الإجرامي في العديد من دول العالم وخاصة في البلاد الإسلامية والعربية، وحضور فكرها التكفيري وما ترتب عليه من إزهاق للأرواح البريئة وزعزعة الأمن والاستقرار وتدمير للممتلكات وإتلاف للأموال، تعتبير الطامة الكبرى والفتنة العظمى التي تقتضي العلماء والإعلاميين أن يقدّموا المعلومات اللازمة عن الإسلام. تتناول هذه الدراسة دور الإعلام الإسلامي فيما يتعلق بقضية الإرهاب وتهدف إلى كشف أسباب الإرهاب وتوفير حلول لهذه الظاهرة. تطبق الدراسة المنهج التحليلي لإعطاء تفسير تحليلي شامل لهذه المسألة. أخيرًا، وجد هذا المقال أن تورط الإعلام الإسلامي مقترح كحل مهم للغاية لويلات الإرهاب في يومنا هذا. Today, the world is exposed to the scourge of terrorism unprecedented in the history of mankind, and these scourges grows, unfortunately, from the vagaries of organizations, movements and terrorist groups that belong to Islam unlawfully, the intensification of its criminal presence in many countries of the world, especially in the Islamic and Arab countries, and the consequent loss of innocent lives, disturb the security and stability, destruction of property and means, is considered a great disaster and great strife that requires the movement of the Muslim scholars and Media practitioners to provide a necessary information about Islām. This paper deals with the role of Islamic media regarding the issue of terrorism and aims to expose the causes of terrorism and to provide solutions to this phenomenon. The study applies analytical approach to gives a comprehensive analytical interpretation of the issue. Finally, this article found that the involvement of Islamic Media is proposed as a very important solution to the scourge of terrorism in the present day.